The Effect of Exchange Rates on Consumer Price Index - Joseph Musandiwa; Collins C. Ngwakwe (Облік і фінанси, 2023)
The consumer price index (CPI) is a crucial economic indicator of consumer price inflation, which has an attendance effect on the extent of savings and, hence, on investment capacity. The literature contains different opinions on the relationship between exchange rate and consumer price index; however, given the uniqueness of each country’s economic environment, it became apposite to focus the bearing of this paper on the South African economic context. Thus, this paper evaluates the effect of currency exchange rates on the consumer price index in South Africa. Time series data on CPI and exchange rates were drawn from the Fusion Media investment database and were analysed using the OLS regression. For the independent variables exchange rate, which is the Rand price against the Dollar, the authors applied lagg-2 given the assumption that exchange rate differences might take up to two months to affect the consumer price index. The authors’ assumption draws from the findings of eminent scholars, which indicate that, given sufficient time, changes in domestic prices would fully compensate for exchange rate adjustments. The analysis showed that exchange rate changes significantly and positively affect CPI within the data’s boundaries. The findings offer academic and practical implications for understanding the theoretical short-term period effect of the exchange rate on the consumer price index within the South African setting and for practical economic policy application for advanced policies to cushion potential negative effects on savings and investment. The paper provides an agenda for further study of the application of expanded time series to evaluate the effect of currency exchange rates on CPI over a longer period to unravel a theoretical difference between the short-term and long-term implications of exchange rates on CPI.